A social network analysis applied to understand the relationships in fish farming tank-nets business in Brazil - Martinelli, Raiane Real; Pigatto, Gessuir; Queiroz, Timóteo Ramos; Mollo Neto, Mário (Interações, 2019)
The present article aims to analyze the insertion of tilapia tank-nets producers in social networks and their influence on the information transfer within the network, from a group of fish farmers located in a reservoir in southeastern Brazil. Exploratory methods characterize this research, which has a qualitative approach based on a multi-case study. Roster method conducts the network research taking into account the limited number of actors in the network and the identification of all. This article allows an understanding of the influence of frequency, time and value attributed to the exchange of information among fish farmers. The trust degree in the relationships between fish farmers was measured through a Social Network Analysis (SNA) with the help of the UCINET® software. The results show that the transmitters of more information are the same that present themselves as central in the network and those who have the most valuable information.